University Student Responses to the Implementation of the Active Debate Method in the Pancasila Course - Herianto; Marthaliakirana, Angsoka Dwipayana; Abdilah, Hayatining Suci (International Journal of Sustainable English Language, Education, and Science, 2025)
This study aims to determine student responses to the implementation of the active debate method in the Pancasila course. This research is quantitative and descriptive in nature. The subjects of this study were 131 students from the Faculty of Teacher Training and Education at Sultan Ageng Tirtayasa University. The instrument used was an online questionnaire employing a Likert scale (1-5). The research procedure involved asking students who had participated in the active debate method during the Pancasila course to complete an online questionnaire. The questionnaire results were analyzed using quantitative descriptive analysis to ascertain student responses to the use of the debate method. The findings indicate that student responses to the active debate method in the Pancasila course fall under the "Good" category. Student responses for each aspect are as follows: (1) Student activity and participation (Good category); (2) Understanding and analysis of ideological concepts (Good category); (3) Critical thinking and argumentation skills (Good category); (4) Communication and social attitudes (Very Good category); and (5) Effectiveness and general impression of the learning (Good category). It can be concluded that the active debate method is a viable option for lecturers teaching the Pancasila course, helping students gain a deeper understanding of the basic concepts of Pancasila ideology and encouraging active student participation in lectures.